Pengawasan Badan Kesatuan Bangsa dan Politik dalam Tata Kelola Organisasi Kemasyarakatan di Kabupaten Ogan Komering Ilir - Supardi Supardi; Novita Wulandari; Masayu Adiah (Mahesa Research Center, 2026)
This study aims to analyze the implementation of the supervisory function of the National Unity and Politics Agency (Kesbangpol) in the governance of community organizations (Ormas) in Ogan Komering Ilir Regency. The analysis focuses on administrative and substantive supervisory mechanisms, guidance as a preventive instrument, and factors affecting supervisory effectiveness within the context of local government. A qualitative descriptive approach was employed, grounded in theories of public administrative supervision and governance. Data were collected through in-depth interviews, observation, and document analysis, and analyzed interactively through data reduction, data display, and conclusion drawing. The findings indicate that Kesbangpol’s supervision has been implemented in accordance with the regulatory framework through organizational registration and legal verification, activity monitoring, and ideological as well as civic education. However, supervision remains predominantly administrative and has not been substantively optimal due to limited institutional capacity, low administrative compliance among some community organizations, and weak cross-sectoral coordination. Theoretically, this study contributes to the field of Government Studies by conceptualizing the supervision of community organizations as a governance instrument that requires institutional capacity, inter-agency collaboration, and constructive state–civil society relations in local governance.